Photo-organocatalytic Synthesis of β-Keto Sulfonyl Fluorides via Radical Fluorosulfonylation of Vinyl Acetates - Wang, Peng; Li, Shao-Jie; Zhang, Honghai; Yang, Na; Liao, Saihu (Synlett, 2022)
A metal-free synthesis of useful β-keto sulfonyl fluorides has been established via radical fluorosulfonylation of ketone-derived vinyl acetates under photoredox organocatalysis by using 1-fluorosulfonyl benzoimidazolium (FABI) as the fluorosulfonyl radical source and oxygen-doped anthanthrene (ODA) as the photocatalyst. A series of aryl and alkyl β-keto sulfonyl fluorides as well as cyclic analogues can be readily obtained in moderate to high yields from widely available ketone starting materials.
Keywords: sulfonyl fluorides; radical fluorosulfonylation; vinyl acetates; photoredox; organocatalysis